Interprotein interactions are responsible for the confined diffusion of a G-protein-coupled receptor at the cell surface. (1st October 2003) - Daumas, F.; Destainville, N.; Millot, C.; Lopez, A.; Dean, D.; Salomé, L.
Abstract : The monitoring of the movements of membrane proteins (or lipids) by single-particle tracking enables one to obtain reliable insights into the complex dynamic organization of the plasma membrane constituents. Using this technique, we investigated the diffusional behaviour of a G-protein-coupled receptor. The trajectories of the receptors revealed a diffusion mode combining a short-term rapid confined diffusion with a long-term slow diffusion. A detailed statistical analysis shows that the receptors have a diffusion confined to a domain which itself diffuses, the confinement being due to long-range attractive inter-protein interactions. The existing models of the dynamic organization of the cell membrane cannot explain our results. We propose a theoretical Brownian model of interacting proteins that is consistent with the experimental observations and accounts for the variations found as a function of the domain size of the short-term and long-term diffusion coefficients.